Notas sobre la identidad de Pinguicula moranensis H.B.K., con la descripción de una variedad nueva - Zamudio, Sergio (Instituto de Ecología, A.C., 1999)
Based on the type specimen the identity of Pinguicula moranensis H.B.K. is defined with more precision. It is characterized by its lax and extended "winter rosettes", with spathulate leaves rounded or obtuse at the apex; it grows mainly on limestone. The locality called El Puente de Dios is probably the site of origin of the type specimens. The population growing around the ancient Mina de Morán in the Sierra de Pachuca, Hidalgo, is described as a new variety called P. moranensis var. neovolcanica. It ranges along the Eje Volcánico Transversal, and is characterized by their compact "winter rosettes" with lanceolate to oblong-lanceolate leaves of acute apex.